Steep posterior slope of the medial tibial plateau is associated with ramp lesions of the medial meniscus and a concomitant anterior cruciate ligament injury - Yuki Okazaki; Takayuki Furumatsu; Takaaki Hiranaka; Keisuke Kintaka; Yuya Kodama; Yusuke Kamatsuki; Toshifumi Ozaki (Elsevier, 2021)
Background: Medial meniscus (MM) tears are associated with both acute and chronic anterior cruciate ligament (ACL) insufficiency and can lead to degenerative changes in the knee. ACL reconstruction (ACLR) combined with the meniscal repair was reported to result in decreased anterior knee joint laxity with evidence of improved patient-reported outcomes in the long term. However, a subtle tear of the MM posterior segment, also known as a ramp lesion, is difficult to detect on conventional magnetic resonance imaging (MRI) and is frequently missed in ACL-deficient knees. However, there are few studies about the associations between bone geometry and ramp lesion of the MM. This study aimed to compare sagittal medial tibial slope (MTS), medial tibial plateau depth (MTPD), and coronal tibial slope (CTS) between ACL-injured knees with and without ramp lesion of the MM. We hypothesised that patients with ramp lesion of the MM and a concomitant ACL injury have a steeper MTS and shallower MTPD than those without ramp lesion of the MM. Methods: Twenty-seven patients who underwent ACLR (group A), and 15 patients with combined MM repair (group AM) were included in the study. Anterior tibial translation (ATT) was measured under general anaesthesia just before surgery using a knee arthrometer. MRI was performed in the 10°-knee-flexed position. The MTS and MTPD were measured on sagittal view, and the CTS was measured on coronal view. These parameters were compared between the groups. Differences in MRI measurements or patient demographics between the groups were evaluated using the Mann-Whitney U test. Results: No significant difference was observed in demographic data and post-operative side-to-side difference in ATT between both groups. Pre-operative ATT was significantly higher in group AM than in group A (P < 0.05), whereas post-operative ATT was similar in both groups. Further, Pre-operative ATT was significantly higher in patients with MTS ≥5.0° than in those with MTS <5.0° (P < 0.05). In groups A and AM, the MTS were 3.6° ± 1.8° and 6.2° ± 2.9°, the MTPD were 2.0 ± 0.5 mm and 2.1 ± 0.6 mm, and the CTS were 2.5° ± 1.8° and 2.4° ± 1.6°, respectively. Patients in group AM had a significantly steeper MTS compared to those in group A (P < 0.01), whereas MTPD and CTS were nearly the same in both groups. When the MTS cut-off value was set at 5.0°, the sensitivity and specificity for ACL injury with concomitant ramp lesion of the MM were 0.73 and 0.76, respectively. Conclusion: A steep posterior slope of the medial tibial plateau is a risk factor for ramp lesion of the MM associated with an ACL injury. Especially in patients with MTS ≥5.0°, an occult MM ramp lesion should be strongly suspected, and surgeons should prepare for MM repair in combination with ACLR.